CONTINUOUS AUDIT: PENERAPAN DAN PENGENDALIAN PELAKSANAAN FUNGSI AUDIT BERBASIS TEKNOLOGI INFORMASI - Zahirah, Faranisa Rahma; Melenia, Fransisca; Aminy, Adhinda Rachma (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2021)
The Industrial Revolution 4.0 is an era where information technology is developing rapidly and impacts all fields, including auditing, during a pandemic where interactions are limited. Auditors need a more sophisticated audit approach to prepare to present audit reports quickly. This study aims to see the implementation of continuous audits for a more efficient and effective implementation. The method used is a literature study based on scientific articles or credible publications. The conclusion is that continuous auditing is efficient and effective in auditing financial statements. Unfortunately, the application of this approach is constrained in several ways, namely the non-uniformity of information technology used by each client.